(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The main objective of this paper is to describe the overview of simulation and modeling and analysis. Many critical question are answered in this paper .Like What is simulation and modeling and why it is important in our daily lives, in our professional life and in research or even in our personal life? When is simulation and modeling is appropriate or when it is not? So the objective of this module to gain the knowledge about system and its behavior so that a person can transform the physical behavior of system into a Mathematical model that can in turn transform into a efficient algorithm for simulation process.